2012
DOI: 10.1093/rheumatology/kes100
|View full text |Cite
|
Sign up to set email alerts
|

IL-7R low memory CD8+ T cells are significantly elevated in patients with systemic lupus erythematosus

Abstract: Our findings show that SLE patients have increased IL-7Rα(low) EM CD8(+) T cells, possibly contributing to tissue damage through 2B4-mediated cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
2
19
0
1
Order By: Relevance
“…Inhibiting fractalkine or CX3CR1 reduced disease activity in mouse models of RA, SLE and atherosclerosis (5254). The expansion of IL-7Rα low EM CD8 + T cells and increased expression of CX3CR1 on CD8 + T cells were reported in the peripheral blood of patients with SLE and RA, respectively (16, 51). These observations warrant further studies investigating the specific role of CX3CR1 expression by CD8 + T cells in inflammatory diseases.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Inhibiting fractalkine or CX3CR1 reduced disease activity in mouse models of RA, SLE and atherosclerosis (5254). The expansion of IL-7Rα low EM CD8 + T cells and increased expression of CX3CR1 on CD8 + T cells were reported in the peripheral blood of patients with SLE and RA, respectively (16, 51). These observations warrant further studies investigating the specific role of CX3CR1 expression by CD8 + T cells in inflammatory diseases.…”
Section: Discussionmentioning
confidence: 96%
“…The differential expression of IL-7Rα by EM CD8 + T cells was associated with different levels of DNA methylation in the IL7RA gene promoter (15). Expansion of the IL-7Rα low EM CD8 + T cells was found in older adults and patients with systemic lupus erythematosus (SLE), suggesting a potential association of this cell subset with immunosenescence and inflammation (14, 16). However, the exact functional characteristics of IL-7Rα low and high EM CD8 + T cells and the mechanism(s) defining such characteristics are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al assessed the expression of SLAMF4 in a CD8+ T cell subpopulation defined as CCR7− IL‐7Rα low and observed that it was increased in SLE patients . They did not distinguish the CD45RA+ effector memory and CD45RA− terminally differentiated effector memory populations among the CD8+ CCR7− T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The percentages of SLAMF4‐expressing NK cells and monocytes are reduced in patients with SLE compared with healthy controls . In addition, Kim et al reported that the frequency of interleukin‐7 receptor α‐chain (IL‐7Rα) low effector memory CD8+ T cells was increased in patients with SLE and that these cells had higher levels of SLAMF4 expression compared with IL‐7Rα high effector memory CD8+ T cells . Therefore, engagement of SLAMF4 enhanced the cytotoxic function of IL‐7Rα low effector memory CD8+ T cells against target cells.…”
mentioning
confidence: 99%
“…Surprisingly, the Class I-MHC–peptide complex on the target cell can regulate the level of expression of SLAMF4 on virus specific cytotoxic T cells by an internalization mechanism 28 . Functional involvement on the surface of human CD8 + T cells is further indicated by the finding that in patients with systemic lupus erythomatosis the number of SLAMF4 + CD8 cells is dramatically increased suggesting that exhausted memory CD8 + cells partake in this complex autoimmune disease states 3032 . Because functional single nucleotide polymorphism of the human Slamf4 gene are related to the onset of SLE and rheumatoid arthritis 3032 , the data suggest that variations in Slamf4 gene may affect human inflammatory bowel diseases.…”
Section: Discussionmentioning
confidence: 99%